Answer:
(-2x - 1) • (x + 3)
Explanation:
3.2 Factoring 2x2 + 7x + 3
The first term is, 2x2 its coefficient is 2 .
The middle term is, +7x its coefficient is 7 .
The last term, "the constant", is +3
Step-1 : Multiply the coefficient of the first term by the constant 2 • 3 = 6
Step-2 : Find two factors of 6 whose sum equals the coefficient of the middle term, which is 7 .
-6 + -1 = -7
-3 + -2 = -5
-2 + -3 = -5
-1 + -6 = -7
1 + 6 = 7 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, 1 and 6
2x2 + 1x + 6x + 3
Step-4 : Add up the first 2 terms, pulling out like factors :
x • (2x+1)
Add up the last 2 terms, pulling out common factors :
3 • (2x+1)
Step-5 : Add up the four terms of step 4 :
(x+3) • (2x+1)
Which is the desired factorization